Analisis Minat Belajar Siswa SD Pangkalan Mencari Volume Bangun RUang Berbantuan Perangkat Lunak Geogebra - Bunga Permaganti; Sintia Rahayu; Wahyu Setiawan (Journal on Education, 2019)
This study aims to analyze student interest in learning through the GeoGebra program. The method used in this study is a descriptive qualitative method with a population of all elementary school students in Pangkalan Bandung. The sample used in this study was 29 fifth grade elementary school students in Pangkalan in the matter of building volume. The instrument used was the Student Interest Scale with many 20 statement statements that had positive and negative responses about learning using the GeoGebra program. The scale of students 'interest in learning is used to look for responses from respondents on elementary / MI students' interest in learning on the GeoGebra program material. The results of this study indicate a positive response to the learning of the volume of the building using the GeoGebra program with the average response given indicates a strong category with the percentage of results obtained is 66,69%. The average is obtained from the data of each indicator of student interest in learning.